Silk fibroin compound loaded with polyhydroxy phenolic compound as well as preparation method and application of silk fibroin compound

Through the silk fibroin complex loaded with polyhydroxyphenol compounds, the problem of insufficient effect of existing hemostasis materials in large-scale trauma and severe bleeding is solved, and efficient hemostasis, wound healing and versatile effects are achieved.

CN119405873AActive Publication Date: 2025-02-11NANJING UNIV OF TRADITIONAL CHINESE MEDICINE
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411516303.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-01-11
Filing Date
2024-10-29
Publication Date
2025-02-11
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

Existing hemostatic materials are poor in large trauma and severe bleeding, lack of blood-sucking and bleeding ability, and have limited ability to handle irregular wounds.

Method used

Develop a silk fibroin complex loaded with polyhydroxyphenol compounds, prepared by β-sheet conformation transformation of silk fibroin and self-assembly with polyhydroxyphenol compounds. The preferred feed ratio is polyhydroxyphenol compounds: silk Vitamin = 1:4.

Benefits of technology

It has achieved significant improvement in hemostatic and coagulation ability, which is significantly better than polyhydroxyphenol compounds and silk fibroin itself, and is not cytotoxic and insoluble in the body, has good biodegradability and safety, and has wound healing, antibacterial and anti-aging Multifunctionality such as infection and anti-adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119405873A_ABST
    Figure CN119405873A_ABST
Patent Text Reader

Abstract

The invention provides a silk fibroin compound loaded with a polyhydroxy phenolic compound and a preparation method of the silk fibroin compound, aiming at the defect that the existing hemostatic material has a poor effect on large wounds and serious bleeding, and the silk fibroin compound loaded with the polyhydroxy phenolic compound is prepared by self-assembly of the polyhydroxy phenolic compound and silk fibroin; wherein the silk fibroin is subjected to a beta folding conformation transformation process, the polyhydroxy phenolic compound is preferably an indissolvable compound and most preferably ellagic acid, and the feeding ratio of the polyhydroxy phenolic compound to the silk fibroin is the mass ratio lt; 1: 1, preferably 1: 2-1: 16, and more preferably 1: 4. The hemostatic capacity of the compound is obviously better than that of polyhydroxy phenolic compounds, silk fibroin, Yunnan Baiyao, tranexamic acid, chitosan hemostatic powder and the like. Meanwhile, compared with silk fibroin, the silk fibroin is larger in particle size and heavier in texture, and can quickly settle to a bleeding opening in blood. The compound is free of cytotoxicity, free of hemolysis, capable of being self-degraded in vivo and high in safety. Meanwhile, the hydrogel has the characteristics of wound healing, antibiosis, anti-infection, anti-adhesion and the like, and can be applied to preparation of corresponding preparations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to a silk fibroin complex loaded with polyhydroxyphenol compounds and a preparation method and application thereof. Background Art

[0003] At present, the hemostatic market is dominated by absorbable hemostatic materials, including gauze, sponges, sprays, hemostatic powders, etc., and their main components are mostly natural polymers such as cellulose, chitosan, and fibrin. Their main advantages include short hemostatic time, biodegradability, relatively mild foreign body reaction, no need for secondary surgery to remove, and avoidance of secondary injury to patients. However, their high cost, different absorption time, limited adaptability, and poor effect on large trauma and severe bleeding limit their clinical application. For example, oxidized regenerated cellulose hemostatic materials contain a large number of acidic groups, and the pH reaches 1.7 after being fully saturated with water. In an acidic environment, although they have a certain antibacterial effect, the residual materials may cause a strong inflammatory reaction at the wound and hinder the regeneration of bone tissue, and may even form granulomas and abscesses. Therefore, it is necessary to develop a fast, efficient, economical, and non-toxic absorbable hemostatic material.

[0004] Silk fibroin, a natural polymer protein, is extracted from silk and has excellent in vivo degradability, biocompatibility and anti-inflammatory properties. In terms of hemostasis mechanism, silk fibroin activates coagulation factor XII, thereby triggering the endogenous coagulation cascade reaction. It is a biomacromolecule composed of 5509 amino acids, consisting of a heavy chain (391kDa) and a light chain (26kDa), in which the heavy chain and the light chain are connected by a disulfide bond. When silk fibroin dissolved in LiBr solution or ternary solution is poured into an excess of polar organic solvents such as alcohol, a white suspension of protein complexes will immediately appear. When silk fibroin is kept in solution, due to the multiple interactions between the side chains of silk core protein and salt ions and water molecules, the peptide chain exists in a random coil conformation, i.e., an α-helix. This state is also the natural conformational state of silk fibroin. In this state, silk fibroin has no ability to self-assemble with polyhydroxyphenol compounds, because the benzene ring of the amino acid residue has a large steric hindrance, and polyhydroxyphenol compounds are difficult to integrate into the α-helix structure, so they are exposed on the outside of the silk fibroin molecule. When an antisolvent such as ethanol is used, the peptide chain will be induced to rapidly fold toward a more stable β-sheet assembly. The β-sheet conformation will expose hydrophobic amino acid residues, which can enhance the encapsulation of hydrophobic drugs through hydrophobic interactions and π-π stacking, facilitating subsequent self-assembly with polyhydroxyphenol compounds.

[0005] The silk protein hemostatic drugs currently on the market cannot solve the obstruction of the hydration layer at the blood interface, have a poor adhesion rate to the bleeding wound, and cannot meet the tissue strength adhesion requirements in a wet environment. However, polyhydroxyphenol compounds can form a secondary cross-linked structure with silk protein, thereby recruiting more platelets and solving the possibility of silk protein being washed away by blood. At the same time, polyhydroxyphenol compounds and silk protein can also show a synergistic effect and promote endogenous hemostasis. Summary of the invention

[0006] The purpose of the present invention is to solve the problems of the prior art such as poor effect on large trauma and severe bleeding, insufficient blood absorption and blood seepage ability, and inability to treat irregular wounds, and to provide a silk protein composite loaded with polyhydroxyphenol compounds and a preparation method and application thereof. The technical scheme is as follows:

[0007] The present invention provides a silk fibroin complex loaded with a polyhydroxyphenol compound, which is prepared by self-assembly of the polyhydroxyphenol compound and the silk fibroin; wherein the silk fibroin is treated by a β-folding conformational transformation process, and the feed ratio of the polyhydroxyphenol compound to the silk fibroin is a mass ratio of <1:1, preferably 1:2-1:16, and most preferably 1:4.

[0008] As a further improvement, the polyhydroxyphenol compound is selected from one or more of resveratrol, quercetin, baicalein, kaempferol, lignans, curcumin, ellagic acid, chlorogenic acid, ferulic acid, caffeic acid, syringic acid, sinapinic acid, rutin, myricetin, magnolic acid, fisetin, puerarin, rhein, honeysuckle glycoside, proanthocyanidins, p-coumaric acid, vanillic acid, hesperidin, naringenin, luteolin, genistein, rhein, oleanolic acid, epigallocatechin gallate, acacia glycoside, tea polyphenols, epigallocatechin, salvianolic acid, gallic acid, pyrogallol, catechins, and tannic acid.

[0009] As a further improvement, the polyhydroxyphenol compound is a poorly soluble polyhydroxyphenol compound, preferably one or more of resveratrol, quercetin, baicalein, kaempferol, lignans, curcumin, ellagic acid, chlorogenic acid, ferulic acid, caffeic acid, syringic acid, sinapinic acid, rutin, myricetin, magnolic acid, fisetin, puerarin, rhein, honeysuckle, proanthocyanidins, p-coumaric acid, vanillic acid, hesperidin, naringenin, luteolin, genistein, rhein, oleanolic acid, and epigallocatechin gallate, and ellagic acid is most preferred.

[0010] As the most preferred ellagic acid, the feed ratio of ellagic acid to silk fibroin is preferably 1:2 to 1:16 by mass, and more preferably 1:4 by mass.

[0011] The present invention also provides a method for preparing the above-mentioned silk fibroin complex, comprising two steps of silk fibroin conformation transformation and self-assembly with a polyhydroxyphenol compound: step (1): preparing a silk fibroin solution through a transformation process from an α-helix to a β-folded conformation of the silk fibroin, wherein the conformational change can be achieved by a chemical method or a physical method, wherein the chemical method comprises promoting the transformation by polyols, polylactic acid, metal ions, pH or hydroxypropyl methylcellulose, and the physical method comprises promoting the transformation by high temperature, hydration and pressurization, ultra-low temperature placement, freeze drying, shear force, ultrasound, eddy current, laser irradiation, and high-pressure carbon dioxide treatment; step (2): dissolving or suspending the polyhydroxyphenol compound, and then mixing and stirring the polyhydroxyphenol compound with the silk fibroin solution obtained in step (1) to allow the polyhydroxyphenol compound to self-assemble, thereby obtaining a silk fibroin complex loaded with the polyhydroxyphenol compound. In step (1), preferably, a polyol is used to promote the transformation of the β-folded conformation of the silk fibroin, and more preferably, the polyol is ethanol.

[0012] As an improvement to the preparation method, the polyhydroxyphenol compound is a poorly soluble polyhydroxyphenol compound, and in step (2), the poorly soluble polyhydroxyphenol compound is dissolved or suspended in an organic solvent, and the organic solvent is selected from methanol, ethanol, propanol, propylene glycol, glycerol, n-butanol, and isobutanol.

[0013] When the poorly soluble polyhydroxyphenol compound is ellagic acid, the preferred organic solvent is propylene glycol. After the ellagic acid suspension is incubated with silk fibroin in step (2), the final concentration of propylene glycol in the obtained solution is 5-20%, and the most preferred final concentration of propylene glycol is 10%.

[0014] The present invention provides an application of the silk fibroin complex in preparing a preparation having hemostatic efficacy, which comprises the silk fibroin complex and a pharmaceutically acceptable excipient. The dosage form of the preparation includes gauze, sponge, spinning, spray, powder, granule, gel, sealant, ointment, film, patch, and embolic agent.

[0015] The present invention also provides the use of the silk fibroin complex in preparing a preparation having wound healing, and / or anti-infection, and / or anti-adhesion effects, comprising the silk fibroin complex and a pharmaceutically acceptable excipient.

[0016] The beneficial effects of the present invention are:

[0017] The silk protein complex loaded with polyhydroxyphenol compounds developed by the present invention is an effective hemostatic agent, and its hemostatic and coagulation ability is significantly better than that of polyhydroxyphenol compounds and silk protein itself, indicating that the two materials have a synergistic effect, and the hemostatic effect of the hemostatic agent is significantly better than that of a variety of hemostatic products on the market, such as Yunnan Baiyao, tranexamic acid, chitosan hemostatic powder, etc. The silk protein complex provided by the present invention has a larger particle size, heavier texture, more stable mechanical strength and strong wet tissue adhesion than its silk protein, and has a faster sedimentation rate in the blood than other drugs, and is easy to quickly settle to the bleeding port, while the powder texture of Yunnan Baiyao, tranexamic acid, chitosan hemostatic powder, and silk protein is lighter, and it is easier to float on the surface of the whole blood and thus be washed away by the blood flow, thereby affecting its hemostatic effect. The silk protein complex hemostatic agent is non-cytotoxic, non-hemolytic, self-degradable in vivo, and highly safe. At the same time, the silk protein complex also has the effects of wound healing, antibacterial, anti-infection, and anti-adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The present invention will be further described below in conjunction with the accompanying drawings:

[0019] Figure 1 Fourier transform infrared spectroscopy (FTIR).

[0020] Figure 2 to Figure 4 Comparison of blood viscosity (n=3), Figure A: *, compared with the blank control group, *P<0.05, **P<0.01, ***P<0.001; #, compared with the β-SF-EA group, #P<0.05, ##P<0.01, ###P<0.001. Compared with the β-SF-polyhydroxyphenol compound group, *P<0.05, **P<0.01, ***P<0.001, for example: compared with the β-SF-EA group, *P<0.05, **P<0.01, ***P<0.001.

[0021] Figure 5 Comparison of coagulation time (n=3), *, compared with the β-SF-EA group, *P<0.05, **P<0.01, ***P<0.001.

[0022] Figure 6 Comparison of drug loading (n=3). *, compared with β-SF-EA group, *P<0.05, **P<0.01, ***P<0.001; ND means Not Detected.

[0023] Figure 7-Figure 8 Comparison of drug loading (n=3). *, compared with the water group, *P<0.05, **P<0.01, ***P<0.001.

[0024] Fig. 9 Fourier transform infrared spectroscopy (FTIR) analysis showed that the physical mixture of EA and β-SF was 1:1 (w / w).

[0025] Fig.10 Molecular docking diagram. L74 represents Leu (leucine) at position 74, and D27 represents Asp (aspartic acid) at position 27.

[0026] Fig.11 Characterization: (A) FTIR spectroscopy, (B) XRD, (C) TG, (D) 1H NMR.

[0027] Fig.12 Blood adsorption experiment. Among them, a is blank, b is β-SF, c is EA, d is Yunnan Baiyao, e is tranexamic acid, and f is β-SF-EA. Fig.13 Same as in China.

[0028] Fig.13 Diagram of the test tube tilt coagulation experiment.

[0029] Fig.14 BCI graph of blood coagulation index (n=3).

[0030] Fig.15 Rat tail amputation experiment. Figure A shows the bleeding of rats immediately after tail amputation with drug powder, and Figure B shows the bleeding time after tail amputation; *, compared with the β-SF-EA group, *P<0.05, **P<0.01, ***P<0.001.

[0031] Fig.16 Bleeding time of rat liver and femoral artery (n=3). *, compared with β-SF-EA group, *P<0.05, **P<0.01, ***P<0.001.

[0032] Fig.17 Relative cell proliferation rate of LO2 cells and L929 cells after incubation with drugs for 48 hours (n=6).

[0033] Fig.18 In vitro degradation of β-SF-EA (n=3).

[0034] Fig.19 Characterization of ellagic acid loaded silk fibroin nanoparticle hemostatic powder (β-SFN-EA).

[0035] Fig. 20 Bleeding time of the auricular artery, liver, and femoral artery of rabbits (n=6).

[0036] Fig.21 Bleeding volume of the rabbit's auricular artery, liver, and femoral artery (n=6).

[0037] Fig. 22 In vivo biocompatibility: H&E and Masson's trichrome staining of the surrounding tissues isolated 7, 15, and 30 days after subcutaneous implantation of the material.

[0038] Fig.23 Comparison of wound closure rate (n=3), *, compared with blank control group, *P<0.05, **P<0.01, ***P<0.001; #, compared with β-SF-EA group, #P<0.05, ##P<0.01, ###P<0.001.

[0039] Fig.24 Wound H&E staining.

[0040] Fig.25 H&E staining of rabbit femoral artery wound.

[0041] Fig.26 Comparison of liver healing rate (n=3), *, compared with β-SF-EA group, *P<0.05, **P<0.01, ***P<0.001. DETAILED DESCRIPTION

[0042] Example 1 Preparation of polyhydroxyphenol compound-loaded silk fibroin complex (β-SF-polyhydroxyphenol compound)

[0043] Step (1) Transformation of the β-folded conformation of silk fibroin: dilute silk fibroin (SF) with water by 5 to 10 times and then slowly pour it into an excess of vigorously stirred organic solvent, stir for 2 to 4 hours to complete the transformation of the β-folded conformation, remove the liquid portion by mechanical separation methods such as filtration, centrifugation, and membrane filtration, and repeatedly wash the remaining portion and then freeze-dry to obtain β-folded silk fibroin (β-SF), wherein the organic solvent is selected from methanol, ethanol, propylene glycol, butylene glycol, etc., preferably ethanol; the mechanical separation method is preferably high-speed centrifugation, such as high-speed centrifugation at 10,000 rpm for 15 to 20 minutes.

[0044] Fourier transform infrared spectroscopy (FTIR) analysis: 5% of the sample was mixed with 95% KBr and ground into fine powder, and then scanned by transmission using a FTIR spectrometer (Nicolet is5). Each spectrum was obtained in transmission mode (ten scans) with a resolution of 4 cm -1 , the spectral range is 4000-500cm -1 The FTIR spectrum of the relatively high level of β-sheet structure is at 1615-1640 cm -1 、1510-1525cm -1 The FTIR spectrum of SF in its natural state shows a sharp peak at 1640-1660 cm -1 、1535-1542cm-1 A sharp peak is shown at α-SF. Figure 1 The results show that the characteristic peak of natural α-SF is 1642 cm -1 and 1535cm -1 The characteristic peak of SF after treatment in step (1) is 1620 cm -1 and 1517cm -1 , it can be seen that SF has completed the conformational transition of β-folding and become β-SF.

[0045] Step (2) Self-assembly of polyhydroxyphenol compounds and silk fibroin: The β-SF obtained in step (1) is prepared into a suspension with water and placed in a magnetic stirrer at 500-2000 rpm; the polyhydroxyphenol compound is dissolved or suspended with a solvent, wherein water is used as a solvent for water-soluble polyhydroxyphenol compounds and water or an organic solvent such as ethanol, propylene glycol, or butylene glycol is used as a solvent for poorly soluble polyhydroxyphenol compounds; the prepared solution or suspension is added dropwise to the β-SF suspension, and the mixture is stirred for 12-48 hours to obtain a silk fibroin complex loaded with polyhydroxyphenol compounds.

[0046] The polyhydroxyphenol compound is selected from water-insoluble polyhydroxyphenol compounds, including ellagic acid (EA), resveratrol (RES), quercetin (QUE), baicalein (BAE), kaempferol (KAE), lignan (Lignan), curcumin (CUR), chlorogenic acid (CGA), ferulic acid (FA), caffeic acid (CFA), syringic acid (SA), sinapic acid (Sinapic Acid), rutin (RUT), myricetin (MYR), magnolic acid (Magnolol Acid, MA), Fisetin (FIS), Puerarin (PUE), Rhein (RHE), Lonicerin (Lon), Proanthocyanidins (PC), p-Coumaric Acid (p-CA), Vanillic Acid (VA), Hesperetin (Hes), Naringenin (NAR), Luteolin (Luteolin), Genistein (Gen), Emodin (Emo), Oleanolic Acid (Ola), Danshensu (DS), Epigallocatechin gallate (EGCG); Water-soluble polyhydroxyphenol compounds, including Gallic Acid (GA), Pyrogallic Acid (PGA), Acid, PA), catechin (C), tannic acid (TA), tea polyphenols (TP), acacia glycoside (Acaciin), epigallocatechin (EGC), etc.

[0047] Example 2 Preparation of Silk Fibroin Composites Loaded with Polyhydroxyphenol Compounds

[0048] The difference from Example 1 is that the organic solvent in step (1) is ethanol, and the mechanical separation method is high-speed centrifugation at 10000rpm for 15-20min. In step (2), equal amounts of polyhydroxyphenol compounds and silk fibroin are added, and in the preparation of the polyhydroxyphenol compound suspension, water is used as a solvent for water-soluble polyhydroxyphenol compounds, and water or an organic solvent is used as a solvent for sparingly soluble polyhydroxyphenol compounds, and the mechanical separation method is to take the precipitate after high-speed or ultra-high-speed centrifugation. Add step (3) of drying into powder: the solution obtained in step (2) is dried into powder after removing liquid by mechanical separation methods such as suction filtration, centrifugation, membrane, sedimentation, etc., or a spray dryer or other drying equipment is used to powder in one step, so as to obtain a silk fibroin complex loaded with polyhydroxyphenol compounds; the mechanical separation method is preferably to take the precipitate after high-speed or ultra-high-speed centrifugation.

[0049] Using poorly soluble polyhydroxyphenol compounds as raw materials: ellagic acid-silk protein complex (β-SF-EA), resveratrol-silk protein complex (β-SF-RES), quercetin-silk protein complex (β-SF-QUE), baicalin-silk protein complex (β-SF-BAE), kaempferol-silk protein complex (β-SF-KAE), lignan-silk protein complex (β-SF-Lignan), curcumin-silk protein complex (β-SF-CUR), chlorogenic acid-silk protein complex (β-SF-CGA), ferulic acid-silk protein complex (β-SF-FA), caffeic acid-silk protein complex (β-SF-CFA), syringic acid-silk protein complex (β-SF-SA), sinapinic acid-silk protein complex (β-SF-Sinapic acid-silk protein complex (β-SF-Sinapic acid-silk protein complex) were prepared. Acid), rutin-silk protein complex (β-SF-RUT), myricetin-silk protein complex (β-SF-MYR), magnoliic acid-silk protein complex (β-SF-MA), fisetin-silk protein complex (β-SF-FIS), puerarin-silk protein complex (β-SF-PUE), rhein-silk protein complex (β-SF-RHE), honeysuckle glycoside-silk protein complex (β-SF-Lon), proanthocyanidin-silk protein complex (β-SF-PC), p-coumaric acid-silk protein complex (β-SF-p-CA), vanillic acid-silk protein complex (β-SF-VA), hesperidin-silk protein complex (β-SF-Hes), naringenin-silk protein complex (β-SF-NAR), luteolin-silk protein complex (β-SF-Lut), genistein -Silk fibroin complex (β-SF-Gen), rhubarb-silk fibroin complex (β-SF-Emo), oleanolic acid-silk fibroin complex (β-SF-Ola), salvianol-silk fibroin complex (β-SF-DS), epigallocatechin gallate-silk fibroin complex (β-SF-EGCG); using water-soluble polyhydroxyphenol compounds as raw materials, gallic acid-silk fibroin complex (β-SF-GA), pyrogallol-silk fibroin complex (β-SF-PA), catechin-silk fibroin complex (β-SF-C), tannic acid-silk fibroin complex (β-SF-TA), acacia glycoside-silk fibroin complex (β-SF-Acaciin), epigallocatechin-silk fibroin complex (β-SF-EGC), tea polyphenols-silk fibroin complex (β-SF-TP) were prepared.

[0050] Example 3 Investigation of blood coagulation effect

[0051] The obtained β-SF-polyhydroxyphenol compounds were prepared into 2 mg / mL test solution with normal saline for investigation of coagulation effect: blood was collected from the abdominal aorta of New Zealand white rabbits and placed in a sodium heparin anticoagulant tube, 2 mL of the test solution was added to the tube, normal saline was used as a control, mixed well, incubated at 37°C for 15 min, and then the whole blood viscosity was detected with an automatic blood rheometer (all operations were completed within 2 h after blood collection).

[0052] Whole blood viscosity is the result of friction between blood cells and plasma protein molecules when blood flows, and is the most important indicator in blood rheology. When blood viscosity increases, it means that blood flow is obstructed, while the deformability of red blood cells decreases and aggregation increases, the flow of blood into microvessels and capillaries decreases, and the passing capacity decreases. Figures 2 to 4 The results showed that the silk fibroin complex loaded with polyhydroxyphenol compounds (β-SF-polyhydroxyphenol compounds) could significantly increase the whole blood viscosity compared with the blank group (P<0.05), and was significantly better than the effect of β-SF and the original compound itself (P<0.05), indicating that the formation of the complex can significantly enhance the coagulation effect; and overall, the effect of the self-assembled complex of silk fibroin and insoluble polyhydroxyphenol compounds was better than its self-assembled complex with water-soluble polyhydroxyphenol compounds.

[0053] Weigh 0.1g of the drug powder to be tested and place it in a 1.5mL centrifuge tube. At the same time, measure 0.5mL of anticoagulated blood and add it to the centrifuge tubes containing different drugs. Place them vertically on the laboratory workbench and start timing. After 30s, rotate the inverted centrifuge tube to observe whether the blood flows. Repeat the operation until the anticoagulated blood cannot flow, stop timing, and record it as the coagulation time. Figure 5 The results showed that Figures 2 to 4 The results show a similar trend.

[0054] Among all the complexes, β-SF-EA has the best coagulation effect. This may be related to the multiple hydrogen bonds and planar structure of EA. On the one hand, the existence of multiple hydrogen bonds increases the synergistic effect between hydrogen bonds and further improves the stability of hydrogen bonds; on the other hand, ellagic acid has a symmetrical catechol structure and a planar structure, which can form intramolecular and intermolecular hydrogen bonds, thereby enhancing the rigidity of the complex molecules. This stable molecular structure can reduce the dynamic changes of the molecules, thereby indirectly improving the stability of the intermolecular hydrogen bonds.

[0055] Example 4 Preparation of polyhydroxyphenol compound-silk fibroin complex (α-SF-polyhydroxyphenol compound)

[0056] The difference from Example 2 is that step (1) is deleted, and in step (2), β-SF is replaced by untreated SF, i.e., SF with a natural α-helical conformation. In step (2), equal amounts of polyhydroxyphenol compounds and silk fibroin are added to prepare a polyhydroxyphenol compound-α-silk fibroin complex, which is called α-SF-polyhydroxyphenol compound.

[0057] Example 5 Preparation of polyhydroxyphenol compound-silk fibroin complex (SH-SF-polyhydroxyphenol compound)

[0058] The difference from Example 2 is that the following method is used in step (1): dissolving silk fibroin in an aqueous solution containing tri(2-carboxyethyl)phosphine hydrochloride, placing it at room temperature for a reduction reaction for 5 minutes, and obtaining a SF solution with a concentration of 1.0-5.0wt% treated by a reduction reaction. The rest is the same as the method in Example 2, wherein in step (2), equal amounts of polyhydroxyphenol compounds and silk fibroin are added, and the resulting polyhydroxyphenol compound-silk fibroin complex is called SH-SF-polyhydroxyphenol compound. This method uses a method of destroying disulfide bonds to expose hydrophobic amino acids to combine polyhydroxyphenol compounds such as ellagic acid.

[0059] Example 6 Self-assembly performance study

[0060] The polyhydroxyphenol compound uses ellagic acid as a model drug, and three ellagic acid-silk protein complexes are prepared according to the steps in Examples 2, 4, and 5, wherein the solvent of EA is water, namely β-SF-EA, α-SF-EA, and SH-SF-EA. The assembly efficiency is evaluated by drug loading and encapsulation efficiency, which are calculated by formula 1) and formula 2) respectively, wherein the "amount of EA in the silk protein complex" on the molecule is calculated by the difference method, that is, the amount of EA is subtracted from the free amount after co-incubation with SF. The EA content is analyzed by high performance liquid chromatography (HPLC), and the chromatographic column uses a Hedera C18 column, the mobile phase is acetonitrile: water = 20:80 (v / v), the flow rate is 1.0 mL / min, the detection wavelength is 254 nm, the injection volume is 10 μL, and the spectrum acquisition time is 15 min. The drug loading and encapsulation efficiency are calculated using the following formula:

[0061] Drug loading = amount of EA in silk fibroin complex / total amount of SF and EA (Formula 1)

[0062] Encapsulation efficiency = amount of EA in silk protein complex / EA dosage (Formula 2)

[0063] Depend on Figure 6The results show that the drug loading is: β-SF-EA>SH-SF-EA>>α-SF-EA, among which the drug loading of β-SF-EA reaches 9.6%, while EA is almost undetectable in α-SF-EA, indicating that the efficiency of self-assembly of α-helical silk protein and ellagic acid is very low, highlighting the necessity of conformational flipping of silk protein; SH-SF-EA uses the destruction of disulfide bonds in silk protein molecules to expose its hydrophobic amino acids, thereby completing self-assembly with ellagic acid, but the drug loading is only 4.5%, much lower than β-SF-EA (P<0.001).

[0064] Example 7 Study on the effect of solvent on EA drug loading

[0065] Ellagic acid was used as a model drug for the polyhydroxyphenol compound, and β-SF-EA was prepared by the steps in Example 2. In step (2), water, ethanol, propylene glycol, butylene glycol and other solvents were used as solvents to prepare the polyhydroxyphenol compound suspension. If an organic solvent was used as the suspension solvent, the final concentration of the organic solvent in the solution obtained after the polyhydroxyphenol compound suspension was incubated with β-SF was 10%. The drug loading capacity was investigated by the method in Example 6. Figure 7 The results showed that the addition of organic solvents effectively increased the drug loading of ellagic acid, among which propylene glycol > butylene glycol > ethanol > water. The drug loading was the highest when propylene glycol was used, reaching 19.57±1.01%.

[0066] Next, the effect of propylene glycol concentration on the drug loading of EA was investigated. In step (2), propylene glycol was used as a solvent to prepare EA suspension. After incubation with β-SF, the final concentrations of propylene glycol in the obtained solutions were 0%, 5%, 10%, 15%, and 20%, respectively. Figure 8 The results showed that the drug loading of the propylene glycol aqueous solution group was better than that of the water group, among which the 10% propylene glycol aqueous solution group had the best effect, with a drug loading of 19.57±1.01%.

[0067] Example 8 Investigation of different EA:SF feed ratios

[0068] Ellagic acid was used as a model drug for polyhydroxyphenol compounds, and β-SF-EA was prepared using the steps in Example 2, wherein step (2) used propylene glycol as a solvent to prepare an EA suspension, and the final concentration of propylene glycol in the solution obtained after co-incubation with β-SF was 10%; at the same time, the feed ratio of EA to β-SF was controlled to be EA:β-SF=1:0.5, 1:1, 1:2, 1:4, 1:8, 1:12, 1:16 (w / w). As shown in Table 1, the drug loading and encapsulation efficiency of EA were almost not observed for EA:β-SF=1:0.5 and 1:1, while they could be observed for other groups; at the same time, the samples of each group were analyzed by Fourier transform infrared spectroscopy using the method in Example 1 ( Fig. 9), it can be seen that the EA hydroxyl peak (3471cm) was observed in the EA:β-SF=1:2, 1:4, 1:8, 1:12, 1:16 (w / w) groups. -1 ) disappeared, indicating that EA and β-SF have completed hydrogen bonding and self-assembled successfully, but the EA:β-SF=1:0.5, 1:1 group and its physical mixed group still have EA hydroxyl peaks, and the self-assembly of the two molecules cannot be achieved. The above results show that the self-assembly of β-SF and EA can only be achieved when the feed ratio EA:β-SF<1:1 (w / w), among which EA:β-SF=1:4 can achieve the maximum value of EA drug loading and encapsulation efficiency (Table 1), which is called the optimal feed ratio.

[0069] The method in Example 3 was further used to investigate the effects of different EA:β-SF feed ratios on whole blood viscosity. The results in Table 2 showed that the EA:β-SF<1:1 groups significantly increased whole blood viscosity at low, medium, and high shear rates compared with the normal saline group (P<0.5), and were higher than the EA and β-SF groups (P<0.5), indicating that the β-SF-EA prepared with an EA:β-SF<1:1 feed ratio had significant coagulation efficacy, and that EA and β-SF enhanced synergistically; among them, EA:β-SF=1:4 had the best coagulation effect.

[0070] In summary, the preparation process of β-SF-EA is to use β-folded SF for preparation, and the feed ratio EA:β-SF<1:1 (w / w), and the specific steps are shown in Example 1; wherein the optimal process is EA:β-SF=1:4 (w / w), and the ellagic acid in step (2) is used as a solvent to prepare a suspension, and the final concentration of propylene glycol in the obtained solution after incubation with SF is 10%. The self-assembly of EA and β-SF cannot be achieved without the transformation of the β-folded conformation of SF or the feed ratio EA:β-SF≥1:1. When EA:β-SF=1:2 (w / w), the drug loading and encapsulation efficiency are both low, indicating that although the self-assembly of EA and β-SF can be achieved at this time, the loss is large.

[0071] Table 1 Effect of the feed ratio of β-SF to EA on drug loading and encapsulation efficiency (n=3)

[0072]

[0073] ND means Not Detected.

[0074] Table 2 Effect of different EA:β-SF feed ratios on whole blood viscosity (n=3)

[0075]

[0076]

[0077] *: Compared with the saline group, *P<0.05, **P<0.01, ***P<0.001; #: Compared with the EA:β-SF=1:4 group, #P<0.05, ##P<0.01,

[0078] ###P<0.001.

[0079] Example 9 Molecular docking of silk fibroin complex

[0080] Computer simulation study on the binding mode of ellagic acid and silk fibroin was performed. After obtaining the silk fibroin heavy chain crystal structure from PDB bank (PDB number: 3UA0), due to the lack of previous studies on the binding mode, we In 2018, the SiteMap module was used to predict the binding sites. After hydrogenation of the silk protein crystal structure and removal of irrelevant ions, the ellagic acid small molecule was converted into a 3D conformation via the LigPrep module, outputting up to 32 isomers, and finally Glide extraprecision (XP) was used to output 20 binding poses. Fig.10 As shown, after the two phenolic hydroxyl groups in the ellagic acid small molecule form hydrogen bonds with L74, they also need to form hydrogen bonds with D27 on another heavy chain, indicating that the continued formation of hydrogen bonds with the other two highly symmetrical hydroxyl groups in ellagic acid can achieve stable binding. In addition, since the heavy chains in the silk fibroin maintain a highly similar β-folded secondary structure, there may not be enough hydrophobic interaction between the ellagic acid small molecule and the two heavy chain proteins to maintain stability. It is reasonable to speculate that the ellagic acid small molecule will be bound and wrapped with at least three to four heavy chain proteins to achieve stable binding. The molecular docking results explain the molecular mechanism of the experimental results of "EA:β-SF<1:1 (w / w) can achieve self-assembly of β-SF and EA" in Example 8.

[0081] The tested samples in Examples 10 to 14 and 22 to 24 were prepared using the optimal process to obtain β-SF-EA.

[0082] Example 10 Characterization of Silk Fibroin Composites Loaded with Polyhydroxyphenol Compounds

[0083] FT-IR confirmed the self-assembly of EA and β-SF ( Fig.11 A): EA hydroxyl peak (3471 cm -1 ) indicates that EA and β-SF may self-assemble through intermolecular hydrogen bonds. X-ray diffraction (XRD) ( Fig.11The characteristic peaks of EA in B) weaken or disappear after combining with silk fibroin, indicating that this is not a simple physical mixture, but a new crystal phase formed by interaction, confirming the FT-IR results; at the same time, the change of crystal form is seen, β-SF shows broad diffraction peaks, indicating that they are amorphous macromolecules; EA shows many strong diffraction peaks, indicating that it is in a crystalline state; after β-SF and EA self-assemble, the peak intensity of EA decreases significantly, and it can be judged that β-SF-EA is mainly amorphous macromolecules.

[0084] Thermogravimetric (TG) curves were evaluated and divided into three stages ( Fig.11 C). In the first stage, from room temperature to 120 ° C, the weight loss is about 6.1%, which is mainly due to the evaporation and desorption of adsorbed water; in the second stage, the weight loss is between 150 ° C and 450 ° C, corresponding to the decomposition of silk protein molecular chains, the decomposition of amino acid residue side chains and the cleavage of peptide bonds, among which the silk I crystal structure (α-helix and random coil) degrades at ~250 ° C, and the silk II crystal structure (β-sheet) degrades at ~260 ° C; β-SF shows a major degradation peak at 260 ° C, and a stable β-fold conformation is formed on the surface; Interestingly, the main degradation peak of β-SF-EA shifts to 280 ° C, indicating that the silk II structure is more stable, which may be due to the strong interaction between EA and protein during the self-assembly process, thereby improving the stability of the complex. In order to determine the optimal amount of EA incorporated into β-SF, proton nuclear magnetic resonance (1H NMR) ( Fig.11 D): In β-SF-EA, the peak associated with EA was significantly attenuated (<0.007), confirming that EA binds to β-SF via catechol hydrogen, further demonstrating their association.

[0085] Example 11 Investigation of blood coagulation effect

[0086] (1) Plasma sample processing

[0087] New Zealand white rabbits were fed adaptively for one week and fasted the night before the experiment. 1% sodium pentobarbital was used at 3 mL kg -1 The anesthetic dose is injected intraperitoneally. After anesthesia, blood is collected from the abdominal aorta using a 5 mL sodium heparin anticoagulant tube. After blood collection, the blood and anticoagulant must be fully mixed and set aside.

[0088] (2) In vitro blood adsorption ability test

[0089] Weigh 0.1g of the drug powder to be tested and place it in a 1.5mL centrifuge tube. At the same time, measure 0.5mL of anticoagulated blood and add it to the centrifuge tubes containing different drugs. Place them vertically on the laboratory workbench and start timing. After 30s, rotate the inverted centrifuge tube to observe whether the blood flows. Repeat the operation until the anticoagulated blood cannot flow and stop timing. Fig.12As shown in the results, β-SF-EA achieved complete adsorption of blood within two minutes, while other groups could not achieve this effect, indicating that the ability of β-SF-EA to adsorb blood was significantly better than the positive control Yunnan Baiyao and tranexamic acid, and was also significantly better than β-SF and EA monomers, indicating that β-SF and EA can synergistically enhance their effects.

[0090] (3) Test tube tilt coagulation test

[0091] Accurately weigh 5.0 mg of the drug powder to be tested and place it in a 10 mL test tube, spreading the powder as much as possible at the bottom of the test tube. Take 1 mL of anticoagulated blood and add it to the test tube, then add 0.2 mol·L -1 Add 25 μL of CaCl2 solution and mix again immediately, and start timing immediately. Let it stand for 1 minute, tilt the test tube every 30 seconds, and stop timing when the blood coagulates and stops flowing. Fig.13 It was observed that the complete blood coagulation time of the β-SF-EA group (2 minutes) was much shorter than that of the Yunnan Baiyao group (5 minutes), the tranexamic acid group (4 minutes 30 seconds), β-SF (5 minutes) and EA (>5 minutes), indicating that β-SF and EA can synergize. This experiment observed that β-SF-EA has a faster coagulation ability than other drugs.

[0092] (4) Blood rheology measurement

[0093] Whole blood viscosity is the result of friction between blood cells and plasma protein molecules when blood flows, and is the most important indicator in blood rheology. When blood viscosity increases, it means that blood flow is obstructed, and at the same time, the deformability of red blood cells decreases and the aggregation increases, the flow of blood into microvessels and capillaries decreases, and the passing capacity decreases. The method in Example 3 was used to measure the viscosity of blood after β-SF-EA acted on blood at 1·s -1 , 30 · s -1 , 100·s -1 , 150 s -1 , 200·s -1 The results in Table 3 show that, regardless of the shear rate, β-SF-EA significantly increased the viscosity of whole blood (P<0.05), and was significantly better than the commercial chitosan hemostatic powder group (P<0.05). The commercial chitosan hemostatic powder in the control group was purchased from the instantaneous composite microporous polysaccharide hemostatic powder of Seikesaisi Biotechnology Co., Ltd., and its main active ingredient is chitosan.

[0094] Table 3 Comparison of whole blood viscosity between β-SF-EA and chitosan (n=3)

[0095]

[0096] *: Compared with the blank group, *P<0.05, **P<0.01, ***P<0.001; #: Compared with the commercial chitosan hemostatic powder group, #P<0.05, ##P<0.01,

[0097] ###P<0.001.

[0098] (4) Blood coagulation index (BCI)

[0099] Prepare different masses of β-SF-EA (10, 20, 30, 40, 50 mg), place them flat in several 50 mL centrifuge tubes, take 0.1 mL of anticoagulated blood and gently drip it on the sample, then immediately drip 0.02 mL of 0.2 mol / L CaCl2 solution, gently add 25 mL of deionized water to the beaker after 5 minutes, centrifuge at 300 rpm for 5 minutes, then take out the solution, and measure its Abs value at a wavelength of 540 nm with an enzyme marker. Set up a control: add 0.1 mL of anticoagulated blood to a beaker, then add 25 mL of deionized water. The Abs value measured at the same wavelength is assumed to be 100 as a reference value, then the coagulation index BCI is: BCI = 100 × A 样品 / A 对照 The BCI index is an indicator of the coagulation effect. The smaller the index, the better the coagulation effect. Fig.14 It shows that increasing the dosage (increasing the concentration in the same volume) will significantly reduce the blood coagulation index (BCI), which means that the coagulation effect is positively correlated with the dosage.

[0100] Example 12 Investigation of hemostatic effect

[0101] Male SD rats (about 250.0 g) were used to evaluate the hemostatic ability of β-SF-EA.

[0102] Rat tail amputation hemostasis experiment: SD rats were anesthetized by intraperitoneal injection of 1% sodium pentobarbital. 6 cm was measured from the end of the rat's tail, and the tail of the rat was cut with surgical scissors. 20 mg of sample powder (β-SF-EA, Yunnan Baiyao, tranexamic acid) was sprinkled on the wound immediately after bleeding, and the time was started from the bleeding.

[0103] Rat liver wound hemostasis experiment: SD rats were anesthetized by intraperitoneal injection of 1% sodium pentobarbital. The anesthetized rats were fixed in a supine position on the dissecting table, and a longitudinal incision was made along the midline of the abdomen to enter the abdominal cavity and expose the right lobe of the rat liver. The peritoneal fluid was blotted with clean gauze, and a parallel wound of about 2.0 cm long and 0.5 cm deep was made on the right lobe of the liver with a blade. After bleeding, the wound was immediately blotted with cotton that had been weighed in advance, and then 20 mg of sample powder (EA, β-SF, β-SF-EA, Yunnan Baiyao, tranexamic acid) was sprinkled on the wound surface, and the timing was started. The wound was first pressed with cotton for 30 seconds to observe whether it was bleeding. If bleeding continued, it was pressed with cotton for another 30 seconds and then observed. This was repeated until no obvious blood stains appeared on the cotton surface, which was considered successful hemostasis. The timing was stopped and the hemostasis time was recorded.

[0104] Rat thigh muscle trauma hemostasis experiment: SD rats were anesthetized by intraperitoneal injection of 1% sodium pentobarbital, and the anesthetized rats were fixed in a supine position on the dissecting table, and the leg hair was shaved with a rat hair scraper. After the inner thigh was disinfected with alcohol, a scalpel was used to cut a muscle wound about 3 cm long and 1 cm deep. The timer started when the wound was bleeding. After bleeding for 5 seconds, 20 mg of sample powder (EA, β-SF, β-SF-EA, Yunnan Baiyao, tranexamic acid) was sprinkled respectively, and the hemostatic effect was observed and the hemostatic time was recorded.

[0105] Fig.15 This is a rat tail amputation experiment. When β-SF-EA was placed on the wound, bleeding stopped quickly, and almost no blood was left on the filter paper. It can significantly promote hemostasis within 30 seconds; the blank group bled for more than five minutes, which lost statistical significance and was not listed in Figure B. As a control, the tranexamic acid group and the Yunnan Baiyao group required more than 4 times the time to stop bleeding, and the amount of bleeding was significantly higher than that of the β-SF-EA group (P<0.05).

[0106] Fig.16 This is a graph of the bleeding time of the rat liver and femoral artery. The femoral artery bleeding in the blank group exceeded five minutes, which lost statistical significance and was not included in the graph. Fig.16 It shows that β-SF-EA can significantly shorten the hemostasis time of the two models, and the hemostatic efficacy is significantly better than Yunnan Baiyao (P<0.05) and tranexamic acid (P<0.05), and is also significantly better than EA (P<0.05) and β-SF group (P<0.05), indicating that silk fibroin and ellagic acid have a synergistic effect, and the above results are consistent with the blood rheology and test tube tilting coagulation results in Example 11. It was observed in both rat bleeding models that β-SF-EA has a faster sedimentation rate in the blood than other drugs, and is easy to quickly settle to the bleeding site, while Yunnan Baiyao, tranexamic acid, and β-SF powders are lighter in texture and are more likely to float on the surface of whole blood and be washed away by the blood flow, thereby affecting their hemostatic effect.

[0107] Example 13 Safety Investigation

[0108] (1) Cell recovery

[0109] Take out the frozen LO2 cells and L929 cells, and gently shake them in a 37℃ water bath until they are completely thawed. In the clean bench, transfer the cell suspension in the cryopreserved tube to a cell culture bottle, and add 4mL of DMEM medium containing 10% fetal bovine serum to the culture bottle. Use a dropper to gently blow to evenly disperse the cells in the culture medium, and then place it in a cell culture incubator at 5% CO2 and 37℃ for culture. After 6 hours of culture, place the culture bottle in the clean bench after alcohol disinfection, remove the old culture medium, and add 4mL of culture medium again after washing, and continue to culture in the cell culture incubator.

[0110] (2) CCK8 quantification method

[0111] 0.2 mg of β-SF-EA and EA were respectively dissolved in 1 mL of DMSO, and gradient concentrations were set up.

[0112] Take the cells in the logarithmic growth cycle, wash them with PBS solution, add trypsin digestion solution to treat the cells into a suspended state, calculate the cell density with a cell counting plate, and calculate 1×10 per well. 5 After cells / mL were inoculated into 96-well plates, they were placed in a cell culture incubator and cultured for 24 hours. After the cells adhered to the wall, the culture medium was aspirated and washed twice with PBS. 100 μL of the experimental group: β-SF-EA and EA extracts, the blank group: DMEM culture medium containing 10% fetal bovine serum, and the positive group: paclitaxel extract were added to the 96-well plates inoculated with cells. Six parallel samples were set up for each group, and then placed in a 37°C, 5% CO2 cell culture incubator for 48 hours. The culture medium was aspirated, washed twice with PBS, and 100 μL of CCK8 solution (90 μL DMEM culture medium + 10 μL CCK8) was added. The plates were placed in an incubator and incubated in the dark for 30 minutes, and then the absorbance (OD) at 450 nm was detected with an enzyme reader. Six parallel samples were repeated at each time point, and the relative cell proliferation rate was calculated according to the following formula: Relative growth rate (RGR) % = OD 实验组 / OD 空白组 *100%.

[0113] The cytotoxicity level was determined according to the cytotoxicity level in Table 4, where the positive control should not be lower than level 3. Cells with a level of 0-1 were considered qualified.

[0114] Table 4 Cell proliferation response grading standard

[0115]

[0116] We investigated the toxicity of β-SF-EA and EA on L929 cells and LO2 cells using CCK8 assay. Fig.17 As shown in the figure, the relative proliferation rate of all β-SF-EA groups was higher than 85%. According to the toxicity grading standard of ISO10993-1, the cytotoxicity of β-SF-EA was 0-1. At the same time, the addition of silk fibroin effectively improved the biocompatibility of ellagic acid. In summary, β-SF-EA does not affect cell proliferation and has good cell compatibility.

[0117] (2) Hemolysis test

[0118] Dilute 8mL of fresh rabbit blood with 10mL of normal saline. Put 20mgβ-SF-EA into a 50mL centrifuge tube, add 10mL of normal saline, and place in a 37℃ water bath for 10min. Then add 0.2mL of diluted rabbit blood, shake gently, and centrifuge at 1000rpm for 5min after 60min of water bath. Take the supernatant and measure the absorbance at 540nm. The positive control group uses 10mL of distilled water plus 0.2mL of rabbit blood, and the negative control group uses 10mL of normal saline plus 0.2mL of rabbit blood. The operation method is the same. Each group is parallel to three times. The hemolysis rate is calculated using the following formula: Hemolysis rate (%) = (absorbance of test sample - absorbance of negative control) / (absorbance of positive control - absorbance of negative control) * 100%.

[0119] Different materials in direct contact with blood may cause red blood cells to rupture and produce hemolysis. The hemolysis test is to evaluate the hemolysis of the material by checking the hemoglobin concentration. After calculation, the hemolysis rate of β-SF-EA is 1.13±0.02% (Table 5). According to GB / T4233.2, a hemolysis rate of less than 5% is qualified. Therefore, the prepared β-SF-EA meets international standards.

[0120] Table 5 Hemolysis rate (n=3)

[0121]

[0122] Example 14 Degradation Performance Investigation

[0123] A certain mass of β-SF-EA was weighed and placed in a PBS solution containing 0.1 μ / mL protease XIV, and incubated at 37°C. A PBS solution without protease XIV was used as a blank sample. The samples (n=3) were incubated in PBS solution and PBS solution containing 0.1 μ / mL protease XIV for 5, 10, 15, 20, 25, and 30 days. All degradation samples were replaced with fresh solutions at a fixed time every day. The degradation products were dried at 60°C, and the samples were weighed to a constant weight. The residual mass retention rate R M The calculation formula is as follows: M / % = M dt / Mi *100%, where M i is the initial mass, M dt is the mass preserved after t days, mg.

[0124] As a hemostatic agent used in vivo and in vitro, it is required to have good biodegradability. Ideally, in the early stage of wound healing, the hemostatic powder can firmly bond the tissues together to avoid cracking. It is best to degrade slowly. As the wound heals, the drug gradually degrades. Finally, the remaining drug components can be completely degraded after the wound heals and absorbed by the human body or excreted through metabolism. The degradation effect of β-SF-EA at 37°C is as follows Fig.18 As shown. It can be found that the degradation rate of β-SF-EA in PBS is slow, and the residual mass at 30 days is 90.11±3.51%. In the PBS solution containing protease XIV, the degradation effect of β-SF-EA can be roughly divided into two stages: the first stage (0-15 days), the degradation rate is slow in this stage, and the residual mass is 67.83±2.25% at 15 days; the second stage (15-30 days), the degradation rate begins to increase significantly, and the residual mass is 24.50±0.70% at 30 days, and most of it is degraded, which shows that it has good degradability.

[0125] Example 15 Preparation of Silk Fibroin Nanoparticles Loaded with Polyhydroxyphenol Compounds (β-SFN-Polyhydroxyphenol Compounds)

[0126] On the basis of Example 1 or Example 2, the silk fibroin complex loaded with polyhydroxyphenol compounds is nano-sized by chemical methods (desolvation, salting out, microemulsion method, etc.), instrumental methods (electrospray, electric field and supercritical fluid technology, etc.) and other methods (polymer blending method, pH modification method, nanoimprinting method) to prepare silk fibroin nanoparticles (β-SFN-polyhydroxyphenol compounds) loaded with polyhydroxyphenol compounds. Then, it can be prepared into a dosage form with hemostatic effect, including gauze, sponge, spinning, spray, powder, granule, gel, sealant, ointment, film, patch, embolic agent.

[0127] Example 16 Preparation of ellagic acid-loaded silk fibroin nanoparticle hemostatic powder

[0128] The silk fibroin is diluted 5 to 10 times with water and then slowly poured into an excess of organic solvent that is stirred vigorously, stirred for 2 to 4 hours to complete the transformation of the β-folding conformation, and the liquid portion is removed by suction filtration, high-speed centrifugation (10,000 rpm high-speed centrifugation for 15 to 20 minutes), dialysis, etc. The remaining portion is repeatedly washed and then freeze-dried to obtain β-folded silk fibroin. The obtained β-SF is prepared into a suspension with water and placed in a magnetic stirrer at 500-2000 rpm, polyphenols are suspended with solvents such as water, ethanol, propylene glycol, and butylene glycol, and the polyphenol suspension is added dropwise to the β-SF suspension, mixed and stirred for 12 to 48 hours, and the obtained solution is filtered, centrifuged, membrane-passed, and other mechanical separation methods are used to remove the liquid portion, and the remaining portion is freeze-dried using a freeze dryer, and the freeze-dried solid is ground and crushed, and then sieved to obtain a hemostatic powder.

[0129] Example 17 Preparation of ellagic acid-loaded silk fibroin nanoparticle hemostatic spray

[0130] After the silk fibroin is diluted 5 to 10 times with water, it is slowly poured into an excessive amount of organic solvent that is stirred vigorously, and stirred for 2 to 4 hours to complete the transformation of the β-folding conformation. The liquid part is removed by suction filtration, high-speed centrifugation (10,000 rpm high-speed centrifugation for 15 to 20 minutes), dialysis, etc. The remaining part is repeatedly washed and then freeze-dried to obtain β-folded silk fibroin. The obtained β-SF is prepared into a suspension with water and placed in a magnetic stirrer at 500-2000 rpm. The polyphenols are suspended with solvents such as water, ethanol, propylene glycol, and butylene glycol. The polyphenol suspension is added dropwise to the β-SF suspension, mixed and stirred for 12 to 48 hours. The obtained solution is removed by mechanical separation methods such as suction filtration, centrifugation, and membrane, and then dissolved in water to prepare a suspension with a mass fraction of 30%, and injected into a pressure-resistant light handheld spray bottle. The can is shaken for 10 seconds and evenly mixed into a hemostatic spray.

[0131] Example 18 Preparation of ellagic acid-loaded silk fibroin nanoparticle hemostatic granules

[0132] After diluting the silk fibroin with water 5 to 10 times, slowly pour it into the vigorously stirred excess organic solvent, stir for 2 to 4 hours to complete the transformation of the β-folding conformation, remove the liquid part by suction filtration, high-speed centrifugation (10000rpm high-speed centrifugation for 15 to 20 minutes), dialysis and other methods, and repeatedly wash the remaining part and then freeze-dry it to obtain the β-folded silk fibroin. The obtained β-SF is prepared into a suspension with water and placed in a magnetic stirrer at 500-2000 rpm. The polyphenol is suspended with water, ethanol, propylene glycol, butylene glycol and other solvents. The polyphenol suspension is added dropwise to the β-SF suspension, mixed and stirred for 12 to 48 hours, and the obtained solution is filtered, centrifuged, membrane and other mechanical separation methods to remove the liquid part, and the remaining part is freeze-dried using a freeze dryer to obtain silk fibroin accumulation particles (β-SF-polyphenol). Finally, the freeze-dried particles are ground, sieved and other treatments as needed to obtain hemostatic granules of the desired particle size.

[0133] In Examples 19 to 22, EA was used as a model drug, and β-SFN-EA powder was prepared by the method in Example 16: a silk fibroin complex (β-SF-EA) was prepared under the optimal process, and β-SFN-EA was prepared by adding a nano-process, wherein the optimal process was EA:β-SF=1:4 (w / w), and the ellagic acid in step (2) was used as a solvent to prepare a suspension, and the final concentration of propylene glycol in the obtained solution after incubation with SF was 10%. At the same time, β-SFN without EA was used as a control.

[0134] Example 19 Characterization of ellagic acid loaded silk fibroin nanoparticle hemostatic powder (β-SFN-EA)

[0135] Fig.19 A shows the macroscopic morphology of silkworm cocoons, β-SFN, and β-SFN-EA, which were examined using a TESCAN MAIA 3GMU field emission scanning electron microscope. Fig.19The scanning electron microscope (SEM) in B shows that the morphology of β-SF and β-SF-EA are both spherical, and the volume and particle size of β-SF-EA are observed to increase. The particle size was measured by dynamic light scattering (DLS) using NANO ZS90. The results in Table 6 show that the average particle size of β-SFN-EA (201.18±2.17nm) is larger than that of β-SFN (170.33±0.15nm), and the ζ potential of both groups of samples is large (<-20mV), indicating that β-SFN-EA tends to remain stable in aqueous solution due to electrostatic repulsion. The polydispersity index PdI of the β-SFN group is <0.1, indicating that the particle size distribution is uniform, and the β-SFN-EA group increases to 0.39±0.05, indicating that the uniformity of the particle size after preparation has decreased. At the same time, it was observed that the texture of β-SFN is light and thin, and it is easy to float in the solution, while the texture of the prepared β-SFN-EA becomes heavy and easy to settle in the solution.

[0136] Table 6 Particle size, PdI, zeta potential (n=3)

[0137]

[0138] Example 20 Hemostatic Effect Investigation

[0139] New Zealand white rabbits (female, 2.5-3.0 kg) were fixed on an iron plate for surgery and anesthetized by intraperitoneal injection of 3% sodium pentobarbital. The positive control was commercial chitosan hemostatic powder, which was purchased from Seikesaisi Biotechnology Co., Ltd. The instantaneous composite microporous polysaccharide hemostatic powder, whose main active ingredient is chitosan.

[0140] Auricular artery hemostasis model: shave the rabbit hair on the back of the rabbit's ear, cut the auricular artery at 7 cm from the tip of the ear, and blood will immediately gush out from the wound. After the blood bleeds freely for 5 seconds, gently wipe the floating blood from the ear wound with a sterilized cotton ball, and immediately sprinkle 150 mg of β-SFN-EA on the bleeding site, gently place the pre-weighed cotton ball vertically on it, and immediately start timing. Every 30 seconds, gently uncover the cotton ball to observe whether bleeding continues. If the wound continues to bleed, continue to hang the cotton ball and observe every 30 seconds until the bleeding stops. Record the bleeding time and use cotton balls to absorb the gushing blood. The control group was treated with 150 mg of commercially available chitosan hemostatic powder, and the blank group was treated only with cotton balls. The other steps were the same as above. After the hemostasis was completed, the cotton balls were weighed and the blood loss was calculated by the differential weight method. The surviving rabbits were euthanized. The experiment was repeated 6 times for each sample and the average value was taken.

[0141] Liver hemostasis model: After the rabbit is anesthetized, the rabbit hair on the abdomen is shaved, the abdomen is facing up, and the abdomen is disinfected with 75% medical alcohol. The abdominal cavity is cut open, the left medial lobe of the liver is pulled out of the abdominal cavity, and placed on the sterilized gauze. A wound with a length of 3.0 cm and a depth of 0.5 cm is cut on the liver. Free bleeding is allowed for 5 seconds, and then 50 mg β-SFN-EA is immediately sprinkled on the bleeding site. The pre-weighed cotton ball is gently placed vertically on it, and the time is immediately started. The cotton ball is gently uncovered every 30 seconds to observe whether bleeding continues. If the wound continues to bleed, the above operation is continued until the bleeding stops, the bleeding time is recorded, and the gushing blood is absorbed with a cotton ball. The control group was treated with 50 mg of commercial chitosan hemostatic powder, and the blank group was treated only with cotton balls. After hemostasis was completed, the cotton balls were weighed, and the blood loss was calculated by the differential weight method. The surviving rabbits were euthanized. The experiment was repeated 6 times for each sample, and the average value was taken.

[0142] Femoral artery hemostasis model: After the rabbit is anesthetized, the abdomen is facing up, the rabbit hair of the hind legs is shaved, the hind legs are disinfected with 75% medical alcohol, and the skin and soft tissue are peeled with a scalpel to show the femoral artery. The femoral artery is directly cut off. After the free bleeding loss for 5 seconds, the floating blood at the wound is gently wiped off with a sterilized cotton ball, and 150mg β-SFN-EA is immediately sprinkled on the bleeding site. The pre-weighed cotton ball is gently placed vertically on it, and the time is immediately started. The cotton ball is gently uncovered every 30 seconds to observe whether the bleeding continues. If the wound continues to bleed, the cotton ball is continued to be hung for 30 seconds until the bleeding stops. The bleeding time is recorded and the gushing blood is absorbed with a cotton ball. The control group was treated with 150mg of commercial chitosan hemostatic powder, and the blank group was treated only with cotton balls. After the hemostasis was completed, the cotton ball was weighed and the blood loss was calculated by the differential weight method. The surviving rabbits were euthanized. The experiment was repeated 6 times for each sample and the average value was taken.

[0143] Fig. 20 and Fig.21 The following are comparison charts of bleeding time and bleeding volume in rabbits.

[0144] There is an artery on the back of the rabbit ear, which is about the same size as the aorta on the arm of an adult. Conventional hemostatic materials are difficult to stop, so it is a good model for testing the hemostatic properties of biomaterials. In the ear artery experiment, the β-SFN-EA group had a significant effect on both bleeding time and bleeding volume (P<0.05). In terms of bleeding time, the average hemostatic time of the chitosan group was 209.0s, and the average hemostatic time of the β-SFN-EA group was 111.5s, which was shortened by 87.44%; in the bleeding volume data, the average bleeding volume of the chitosan group was 6.69g, while the average bleeding volume of the β-SFN-EA group was 2.24g, which was reduced by 198.66%. It can be seen that β-SFN-EA has a more obvious hemostatic effect.

[0145] The human liver has the most abundant blood vessels among all the internal organs, and liver bleeding is also a very difficult problem during surgery. Therefore, it is representative to use the rabbit liver bleeding model to simulate human internal organ bleeding. We made a wound with a length of 3.0 cm and a depth of 0.5 cm on the rabbit liver to induce massive bleeding. β-SFN-EA showed a very obvious absorption of the gushing blood, while the commercial chitosan hemostatic powder group could not do so, with a significant difference (P<0.05). Interestingly, β-SFN-EA not only adhered to the wound to prevent secondary bleeding, but also acted as a resistance barrier to isolate the injured organ from the surrounding tissue to avoid postoperative adhesion. In terms of bleeding time, the chitosan group took an average of 123.2s, while the β-SFN-EA group took 76.0s, which was shortened by 61.84%; in terms of bleeding volume, the chitosan group had an average bleeding volume of 0.35g, and the β-SFN-EA group had an average bleeding volume of 0.07g, which was reduced by 400%.

[0146] Among the bleeding in human limbs, the femoral artery bleeds the fastest and has the highest risk factor. The size of the femoral artery at the root of the thigh of a rabbit is similar to that of the calf artery of an adult. Therefore, it is representative to use the rabbit femoral artery bleeding model to simulate the massive bleeding in human limbs. We created a lethal femoral artery injury model in rabbit surgery. The control group could not achieve visible hemostasis, and even needed to cooperate with compression to stop bleeding to achieve real hemostasis. The β-SFN-EA group could stop bleeding automatically without applying any external force, which was significantly better than the chitosan group (P<0.05). In terms of bleeding time, the chitosan group took an average of 246.0s, and the β-SFN-EA group took an average of 92.0s, which was shortened by 167.39%; in terms of bleeding volume, the average bleeding volume of the chitosan group was 5.67g, and the average bleeding volume of the β-SFN-EA group was 1.64g, which was reduced by 245.73%. In short, the rabbit massive bleeding model confirmed that β-SFN-EA has a significant rapid hemostatic effect.

[0147] At the same time, it was observed in three rabbit bleeding models that β-SFN-EA has a faster sedimentation rate in the blood than other drugs and can quickly settle to the bleeding site. The commercially available chitosan powder is lighter in texture and is more likely to float on the surface of the whole blood and be washed away by the blood flow, thus affecting its hemostatic effect.

[0148] Example 21 In vivo biocompatibility study

[0149] The biocompatibility in vivo was evaluated by subcutaneous implantation in SD rats for 7, 15, and 30 days, followed by histopathological examination. Fig. 22H&E staining showed acute inflammation at the particle / tissue interface after 7 days, decreased inflammation and collagen deposition after 15 days, and no residual material or obvious tissue reaction was observed by 30 days, indicating initial inflammation followed by fibroblast proliferation and accelerated healing, with complete absorption of β-SFN-EA after 30 days.

[0150] Example 22 Investigation of tissue healing effects

[0151] (1) Mouse full-thickness skin defect experiment

[0152] A full-thickness skin defect model was used to evaluate the effect of a single use of β-SF-EA on the subsequent skin wound healing effect. C57B mice were divided into a blank group, a β-SFN-EA group, a chitosan group, and a Johnson & Johnson Speed ​​Gauze group. The mice were anesthetized using an air anesthesia machine, the back hair was removed, and the back area was disinfected with iodine and alcohol. Subsequently, the healing pad was sutured to the back of the mouse, and a circular skin defect (d = 8 mm) was established in the back pad of each mouse using a skin punch. On day 0, 10 mg of the drug was administered to each group, and the blank group was not treated. All wounds were fixed with breathable medical dressings to prevent the movement of the drug. The wounds were photographed and the dressings were changed with a digital camera on days 0, 3, 7, and 14, and the wound size was measured using Image J software. Wound healing rate (%) = ((A o -A t ) / A o )*100% of which A o is the initial wound area, A t is the wound area at different time points (days 3, 7, and 14). To evaluate the healing process, four mice in each group were randomly euthanized on days 3, 7, and 14, and the skin and muscle tissues at the wound site were sampled and fixed in 4% paraformaldehyde for 24 h. The harvested skin was then embedded in paraffin and stained with H&E and Masson's trichrome. The healing was evaluated by analyzing epithelial thickness, integrity, scab, neovascularization, inflammatory cells, and collagen fiber deposition. The density of collagen deposition was quantified using Image J software. Immunofluorescence detection of interleukin-6 (IL-6) and vascular endothelial growth factor (VEGF) was applied to explore the anti-inflammatory and angiogenic effects of β-SFN-EA on the wound area. Immunohistochemical staining was used to detect the expression of IL-6, tumor necrosis factor-α (TNF-α), and platelet endothelial cell adhesion molecule-1 (CD31) in the skin wound. Positive markers were analyzed using Image J software.

[0153] like Fig.23As shown, the calculated wound closure rate on the 0th, 3rd, 7th and 14th days intuitively reflects the therapeutic effect. After 3 days of treatment, the wound area of ​​each group was reduced to a certain extent. Compared with the β-SF-EA group, the wound closure rate of the blank group was the smallest, indicating the worst healing effect. In contrast, among the chitosan group and the Johnson & Johnson yarn group, the wound closure rate of the β-SF-EA group was the highest. On the 7th day, the healing rate of the β-SF-EA group was still the highest level of all groups on the 7th day, indicating the best therapeutic effect. It can be seen on the H&E stained sections after 7 days of healing ( Fig.24 ): Compared with the blank group, the chitosan group generated a large number of fibroblasts but did not completely fill the defective tissue. New capillaries appeared sporadically in the granulation tissue, showing a certain repair effect. At the same time, a large number of inflammatory cells appeared around the original blood vessels, and the overall slice morphology was irregular; compared with the blank group, the Johnson Speed ​​Yarn group showed obvious tissue damage in the slices accompanied by inflammatory cell infiltration, and no large number of fibroblasts and granulation tissue were formed, with no obvious repair ability; compared with the blank group, the β-SF-EA group not only generated a large number of fibroblasts and granulation tissue, but also densely distributed new capillaries, which was beneficial to the repair of the wound surface. Compared with the three, Johnson Speed ​​Yarn had the weakest repair effect, chitosan was slightly stronger but the inflammatory cell infiltration was serious and the tissue was not completely repaired, and the β-SF-EA group had the best repair effect, with a mild inflammatory reaction, and more fibroblasts and granulation tissue, which was beneficial to the repair process. On the 15th day, the number of fibroblasts and granulation tissue in the chitosan group further increased, and the increase in new capillaries was beneficial to the process of wound repair. However, the overall section was still not regular enough, and the inflammation was alleviated compared with the 7th day. In the Johnson & Johnson Gauze group, obvious defects were seen, indicating that the Johnson & Johnson Gauze had no repair effect. The fibroblast group and granulation tissue group in the β-SF-EA group decreased compared with the 7th day, the original tissue was restored, and the inflammation was weakened.

[0154] (2) Rabbit femoral artery tissue healing experiment

[0155] New Zealand white rabbits were weighed and anesthetized, fixed with the abdomen facing up, shaved, and the hind legs were disinfected with 75% medical alcohol. The skin and tissue were peeled off with a scalpel to show the femoral artery. A (0.7*25mm) medical blood drawing needle was used to make a non-penetrating arterial gap in the femoral artery. Medical sterile cotton balls were used to absorb the gushing blood, and β-SF-EA was quickly administered. After the bleeding stopped, the intramuscular drugs were removed and the muscle tissue and skin tissue were sutured; the blank group did not use cotton balls to absorb blood, and the rabbits were placed in rabbit cages to revive naturally due to blood loss. After death, the blood was cleaned, the weight was weighed, the blood loss was calculated, the blood vessel specimens were collected, and H&E staining was used to observe the defect of arterial tissue. After 30 days, the rabbits were killed, and the femoral artery tissue was taken for H&E staining to observe the recovery of the arterial layer.

[0156] Depend on Fig.25The results show that on the 30th day, the blood vessels in the β-SF-EA group were almost completely repaired. Although the blood vessels were contracted and narrowed, there was still blood flow, indicating that the blood supply was normal. From the animal performance, the lower limb activities were normal. It can be judged that β-SF-EA has a significant effect in promoting vascular tissue repair while being used for hemostasis of non-penetrating wounds of the rabbit femoral artery.

[0157] (3) Liver tissue healing experiment

[0158] SD rats were anesthetized by intraperitoneal injection of 1% sodium pentobarbital. The anesthetized rats were fixed in a supine position on the dissecting table, and a longitudinal incision was made along the midline of the abdomen to enter the abdominal cavity and expose the right lobe of the rat liver. The peritoneal fluid was blotted with clean gauze, and a parallel wound of about 2.0 cm long and 0.5 cm deep was made on the right lobe of the liver with a blade. After bleeding, the wound was immediately blotted with cotton that had been weighed in advance, and then 20 mg of the sample (β-SF-EA, chitosan, and Johnson Speed ​​Gauze) was administered to the wound surface. The wound was first pressed with cotton for 30 seconds to observe whether it bleeds. If bleeding continues, it is pressed with cotton for another 30 seconds and then observed. This is repeated until bleeding stops. The rat's abdominal cavity is then sutured and the rat is given a collar to prevent biting and kept in a single cage. In order to evaluate the healing process, 4 rats in each group were randomly euthanized on the 3rd, 7th, and 14th days, and the liver tissue at the wound site was sampled and fixed in 4% paraformaldehyde for 24 hours. The harvested skin was then embedded in paraffin and stained with H&E and Masson's trichrome staining to evaluate healing, with particular attention paid to liver fibrotic changes.

[0159] like Fig.26 As shown in the figure, the liver wound healing rate on days 0, 3, 7 and 14 directly reflects the healing effect of each group. After 3 days of treatment, the wound area of ​​each group was reduced to a certain extent. Compared with the chitosan group and the Johnson & Johnson yarn group, the wound closure rate of the β-SF-EA group was the highest and the healing effect was the best. On days 7 and 14, the healing rate of the β-SF-EA group was still the highest among all groups, indicating the best treatment effect. The repair was basically completed by day 30.

[0160] Example 23 Investigation of in vivo anti-adhesion performance

[0161] The in vivo anti-adhesion effect of β-SF-EA was evaluated in the rat lateral wall defect-cecum abrasion model. SD rats were anesthetized with sodium pentobarbital (50 mg / kg) and their abdominal hair was shaved. Then a 5 cm long incision was made along the midline of the abdominal wall with surgical scissors. The cecum was separated and its serosal surface was gently rubbed with sterile surgical gauze until punctate bleeding appeared. A 1 cm × 2 cm peritoneal defect was formed on the corresponding outer side of the abdominal wall with a scalpel. In the β-SF-EA group, 1 mL of β-SF-EA sample was placed on the injured abdominal wall and cecum, 1 mL of sterile saline was sprayed on the wound surface in the negative control group, and the abdominal wall defect was covered with a commercially available polylactic acid anti-adhesion film in the positive control group. Four rats in each group were euthanized after 7 and 14 days, and the peritoneum was opened and adhesions were examined. Adhesions formed between the cecum and the abdominal wall were scored using a standard scoring system (Table 7).

[0162] The negative control group showed severe and irremovable adhesions on days 7 and 14, and weakened adhesion between the abdominal wall and cecum was observed, which may be due to the fact that the commercially available polylactic acid anti-adhesion film was applied in the form of a solid sheet and could not completely cover the traumatized surface, which is a defect of such traditional anti-adhesion barrier materials. The β-SF-EA group showed no signs of adhesion on days 7 and 14. In addition, on day 14, the traumatized abdominal wall and cecum in the β-SF-EA group returned to normal. In Table 7, the β-SF-EA group scored the lowest among the three groups, which shows that the anti-adhesion effect of β-SF-EA is better.

[0163] Table 7 Scores of each group in the standard adhesion score table

[0164]

[0165] Note: Control is the blank group, Film is the commercially available polylactic acid anti-adhesive film, compared with the blank group, *P<0.05, **P<0.05.

Claims

1. A silk fibroin composite loaded with a polyhydroxyphenol compound, characterized in that: The preparation is carried out by self-assembly of polyhydroxyphenol compounds and silk fibroin; the silk fibroin is treated by a β-folding conformational transformation process, and the mass ratio of the polyhydroxyphenol compounds to the silk fibroin is less than 1:

1.

2. The silk fibroin complex according to claim 1, characterized in that: The mass ratio of the polyhydroxyphenol compound to the silk fibroin is 1:2-1:

16.

3. The silk fibroin complex according to claim 2, characterized in that: The mass ratio of the polyhydroxyphenol compound to the silk fibroin is 1:

4.

4. The silk fibroin composite according to any one of claims 1 to 3, characterized in that: The polyhydroxyphenol compound is selected from one or more of resveratrol, quercetin, baicalein, kaempferol, lignans, curcumin, ellagic acid, chlorogenic acid, ferulic acid, caffeic acid, syringic acid, sinapinic acid, rutin, myricetin, magnolic acid, fisetin, puerarin, rhein, honeysuckle glycoside, proanthocyanidins, p-coumaric acid, vanillic acid, hesperidin, naringenin, luteolin, genistein, rhein, oleanolic acid, epigallocatechin gallate, acacia glycoside, tea polyphenols, epigallocatechin, salvianolic acid, gallic acid, pyrogallol, catechins, and tannic acid.

5. The silk fibroin composite according to any one of claims 1 to 4, characterized in that: The polyhydroxyphenol compound is a poorly soluble polyhydroxyphenol compound.

6. The silk fibroin complex as claimed in claim 5, characterized in that: The poorly soluble polyhydroxyphenol compound is selected from one or more of resveratrol, quercetin, baicalein, kaempferol, lignans, curcumin, ellagic acid, chlorogenic acid, ferulic acid, caffeic acid, syringic acid, sinapinic acid, rutin, myricetin, magnolic acid, fisetin, puerarin, rhein, honeysuckle glycosides, proanthocyanidins, p-coumaric acid, vanillic acid, hesperidin, naringenin, luteolin, genistein, rhein, oleanolic acid, and epigallocatechin gallate.

7. The silk fibroin composite according to claim 6, characterized in that: The poorly soluble polyhydroxyphenol compound is ellagic acid.

8. The silk fibroin complex according to claim 7, characterized in that: The mass ratio of ellagic acid to silk fibroin is 1:2-1:

16.

9. The silk fibroin complex according to claim 8, characterized in that: The mass ratio of ellagic acid to silk fibroin is 1:

4.

10. The method for preparing the silk fibroin complex according to any one of claims 1 to 9, comprising two steps of conformational transformation of silk fibroin and self-assembly with a polyhydroxyphenol compound: step (1): silk fibroin is subjected to a transformation process from an α-helix to a β-folded conformation to obtain a silk fibroin solution, wherein the conformational change can be achieved by chemical or physical methods, wherein the chemical method comprises promoting the transformation by polyols, polylactic acid, metal ions, pH or hydroxypropyl methylcellulose, and the physical method comprises promoting the transformation by high temperature, hydration and pressurization, ultra-low temperature placement, freeze drying, shear force, ultrasound, eddy current, laser irradiation, and high-pressure carbon dioxide treatment; step (2): after dissolving or suspending the polyhydroxyphenol compound, mixing and stirring with the silk fibroin solution obtained in step (1) to allow it to self-assemble, wherein the mass ratio of the polyhydroxyphenol compound to the silk fibroin is less than 1:1, thereby obtaining a silk fibroin complex loaded with the polyhydroxyphenol compound.

11. The preparation method according to claim 10, characterized in that: The mass ratio of the polyhydroxyphenol compound to the silk fibroin in step (2) is 1:2-1:

16.

12. The silk fibroin complex according to claim 11, characterized in that: In step (2), the mass ratio of the polyhydroxyphenol compound to the silk fibroin is 1:

4.

13. The preparation method according to any one of claims 10 to 12, characterized in that: The step (1) uses polyol to promote the transformation of the β-folding conformation of silk fibroin.

14. The preparation method according to claim 13, characterized in that: The polyol is ethanol.

15. The preparation method according to any one of claims 10 to 14, characterized in that: The polyhydroxyphenol compound is a poorly soluble polyhydroxyphenol compound, wherein in step (2), the poorly soluble polyhydroxyphenol compound is dissolved or suspended in an organic solvent, and the organic solvent is selected from methanol, ethanol, propanol, propylene glycol, glycerol, n-butanol, and isobutanol.

16. The method according to claim 15, characterized in that: The poorly soluble polyhydroxyphenol compound is ellagic acid, the organic solvent is propylene glycol, and after the ellagic acid suspension is co-incubated with the silk fibroin in step (2), the final concentration of propylene glycol in the obtained solution is 5-20%.

17. The preparation method according to claim 16, characterized in that: The final concentration of propylene glycol is 10%.

18. A silk fibroin complex loaded with polyhydroxyphenol compounds prepared by the preparation method according to any one of claims 10 to 17.

19. Use of the silk fibroin complex according to any one of claims 1 to 9 and 18 in preparing a preparation having hemostatic effect, characterized in that: It comprises the silk fibroin complex according to any one of claims 1 to 9 and 18 and a pharmaceutically acceptable excipient.

20. The use as claimed in claim 19, characterized in that: The preparation with hemostatic effect includes gauze, sponge, spinning, spray, powder, granule, gel, sealant, ointment, film, patch, embolization.

21. Use of the silk fibroin complex according to any one of claims 1 to 9 and 18 in preparing a preparation having wound healing, and / or anti-infection, and / or anti-adhesion effects, characterized in that: It comprises the silk fibroin complex according to any one of claims 1 to 9 and 16 and a pharmaceutically acceptable excipient.

Citation Information

Patent Citations

  • Fibroin medical biological adhesive and preparation method thereof

    CN108744023A

  • Silk fibroin conductive hydrogel and preparation method thereof

    CN110305339A

  • Silk fibroin hemostatic gel as well as preparation method and application thereof

    CN115645597A

  • Method for preparing injectable polyphenol-macromolecule adhesive hydrogel

    CN115651218A

  • Silk fibroin-based hemostatic viscose powder and preparation method thereof

    CN115671374A